2001
DOI: 10.1038/35079030
|View full text |Cite
|
Sign up to set email alerts
|

High critical currents in iron-clad superconducting MgB2 wires

Abstract: Technically useful bulk superconductors must have high transport critical current densities, Jc, at operating temperatures. They also require a normal metal cladding to provide parallel electrical conduction, thermal stabilization, and mechanical protection of the generally brittle superconductor cores. The recent discovery of superconductivity at 39 K in magnesium diboride (MgB2) presents a new possibility for significant bulk applications, but many critical issues relevant for practical wires remain unresolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
260
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(268 citation statements)
references
References 10 publications
6
260
0
2
Order By: Relevance
“…The doping improved the value of J c and its field dependence, but there was no obvious influence of the doping on the general shape of the J c (H ). The detailed description of the preparation of these wires can be found in the literature [2,3,19,20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The doping improved the value of J c and its field dependence, but there was no obvious influence of the doping on the general shape of the J c (H ). The detailed description of the preparation of these wires can be found in the literature [2,3,19,20].…”
Section: Methodsmentioning
confidence: 99%
“…However, chemical incompatibility of ferromagnetic materials with HTS was a major problem, impeding the practical implementation of this concept. After the discovery of superconductivity in MgB 2 , it became clear that the best J c for MgB 2 wires can be obtained with Fe as the sheath material [2][3][4][5][6][7]. Because of this, the concept of magnetic shielding as a way of reducing ac loss and improving J c (H ) was reconsidered for MgB 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This effect could be more dramatic if the Fe additives are at nano-scale. Jin et al have studied the effect of Fe addition on T c and the J c -H characteristics of MgB 2 [2]. They found that 5wt% Fe addition had no effect on T c and a negative effect on J c .…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have already been made concerning the fabrication of superconducting MgB 2 wires and tapes by both in-situ and ex-situ methods [2]. In particular it has already been shown that Fe [3,4] and steel are the most suitable sheath materials to produce high J c , powder-in-tube MgB 2 wires and tapes. It has been found that reducing the starting powder grain size leads to an increase of the critical current density J c and of the irreversibility field.…”
Section: Introductionmentioning
confidence: 99%